2015
DOI: 10.15252/embj.201489838
|View full text |Cite
|
Sign up to set email alerts
|

KIM‐1‐/TIM‐1‐mediated phagocytosis links ATG5‐/ULK1‐dependent clearance of apoptotic cells to antigen presentation

Abstract: Phagocytosis of apoptotic cells by both professional and semiprofessional phagocytes is required for resolution of organ damage and maintenance of immune tolerance. KIM-1/TIM-1 is a phosphatidylserine receptor that is expressed on epithelial cells and can transform the cells into phagocytes. Here, we demonstrate that KIM-1 phosphorylation and association with p85 results in encapsulation of phagosomes by lipidated LC3 in multi-membrane organelles. KIM-1-mediated phagocytosis is not associated with increased RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 77 publications
5
55
0
1
Order By: Relevance
“…42 Recently, we demonstrated that Kim-1 interaction with p85 and subsequent PI3K-dependent signaling pathway play an important role in kidney injury and repair. 37,43 The PI3K/AKT/mTOR pathway is a well known intracellular signaling pathway related to cell growth, proliferation, and survival. 44,45 Thus, it is likely Kim-1 directly binds to p85 and regulates mTOR activity through the AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…42 Recently, we demonstrated that Kim-1 interaction with p85 and subsequent PI3K-dependent signaling pathway play an important role in kidney injury and repair. 37,43 The PI3K/AKT/mTOR pathway is a well known intracellular signaling pathway related to cell growth, proliferation, and survival. 44,45 Thus, it is likely Kim-1 directly binds to p85 and regulates mTOR activity through the AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…During recovery following AKI, resolution of autophagy may promote proliferation necessary for tubular regeneration and repair (49). We have recently reported a pathway by which luminal apoptotic debris, taken up by the proximal tubule through KIM-1 (kidney injury molecule-1)–mediated phagocytosis, is subsequently processed through autophagy with antigens presented to MHC (major histocompatibility complex) to downregulate the inflammatory response (50, 51). However, the role of autophagy in the transition from acute to chronic kidney injury warrants further study.…”
Section: Pathophysiologymentioning
confidence: 99%
“…[211][212][213] A recent study found that kidney injury molecule-1 (KIM-1)/T-cell Ig and mucin domain 1, a phosphatidylserine phagocytosis and scavenger receptor expressed by kidney proximal tubule epithelial cells, is the dominant apoptotic cell phagocytosis receptor in these cells. 214 Originally, upon ligand extracellular recognition, binding and phosphorylation of KIM-1 cytosolic domain interacted with the phosphoinositide 3-kinase pathway and stimulated LC3 lipidation and autophagy induction with progressive appearance of KIM-1-and LC3-positive organelles characteristic of autophagy. Unlike standard LC3-associated phagocytosis described in professional phagocytic cells, KIM-1 expression induced phosphorylation and activation of ULK1/ATG1, which is essential for autophagosome formation.…”
Section: Autophagy In the Tubulointerstitial Compartmentmentioning
confidence: 99%
“…In summary, this cascade described in kidney proximal epithelial cells represents a novel mechanism by which autophagosomes generated in an ULK1-dependent manner target phagosomes for degradation, which has potential pathophysiological implications as kidney injury in mice carrying a nonfunctional mutant KIM-1 results in a worsening of AKI with the accumulation of unphagocytosed apoptotic cells and increased inflammation. 214,215 Beyond the case of AKI, we hypothesize that interplay between KIM-1-mediated phagocytosis, tubular autophagy, and inflammation may play a role in resolution of inflammation, scarring processes, and progression of chronic nephropathies.…”
Section: Autophagy In the Tubulointerstitial Compartmentmentioning
confidence: 99%